2022
DOI: 10.3389/fmicb.2022.990850
|View full text |Cite
|
Sign up to set email alerts
|

Functional interplay between antagonistic bacteria and Rhizoctonia solani in the tomato plant rhizosphere

Abstract: Microbial interactions with plant roots play an imperial role in tomato plant growth and defense against the Rhizoctonia solani. This study performed a field experiment with two antagonistic bacteria (Pseudomonas and Bacillus) inoculated in healthy and Rhizoctonia solani treated soil in tomato rhizosphere to understand the metabolic pattern and microbial function during plant disease suppression. In the present study, we assessed soil and microbial enzymes, bacterial and fungal cell forming unit (CFU), and car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 103 publications
(141 reference statements)
0
15
0
Order By: Relevance
“…Whereas, they substantially contribute to production, food web interactions, and nutrient recycling. They also represent diverse moods of nutrition, such as phagotrophy, phototrophy, symbiosis, saprotrophy, or a combination of these strategies, in a given ecosystem [ 102 , 103 ].…”
Section: Deciphering the Potential Role Of Micro-macro Fauna In Plant...mentioning
confidence: 99%
“…Whereas, they substantially contribute to production, food web interactions, and nutrient recycling. They also represent diverse moods of nutrition, such as phagotrophy, phototrophy, symbiosis, saprotrophy, or a combination of these strategies, in a given ecosystem [ 102 , 103 ].…”
Section: Deciphering the Potential Role Of Micro-macro Fauna In Plant...mentioning
confidence: 99%
“…Aslam et al (2013) investigated the morphological and physiological response of maize hybrids under drought stress. Aslam et al (2013) and Solanki et al (2022) studied drought stress tolerance in crops by using plant growth promoting rhizobacteria. Arun et al (2020) reported the mitigation of drought stress in rice crop by the application of plant growth-promoting.…”
Section: Introductionmentioning
confidence: 99%
“…PGPR colonizes the roots and improves seed germination and plant biomass production . Microorganisms alleviated abiotic stresses by modulating phytohormone levels. , Plant growth, development, and nutrient acquisition were improved by these microbial phytohormones against various environmental stresses including both abiotic and biotic ones. The synthesis of phytohormones is one of PGPR’s other mechanisms for promoting plant growth and alleviating salt stress . Inoculation of PGPR in plants possessing ambient stresses enhances their proline level, which ultimately leads to improved antioxidant activity, thus increasing the production of plant biomass and improved toxicity .…”
Section: Introductionmentioning
confidence: 99%